2019
DOI: 10.7717/peerj.7614
|View full text |Cite
|
Sign up to set email alerts
|

Effects of reflective warning markers on wildlife

Abstract: Light pollution has become one of the top issues in environmental pollution, especially concerning how secondary light pollution, such as from traffic reflective materials, influences animal distribution and behavior. In this study, 15 camera traps were set up at sites with or without reflective warning markers (RWM) in coniferous forests on Cangshan Mountain located in Dali Prefecture, China. The results showed that the number of independent photographs and species at sites without RWMs were significantly hig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 38 publications
0
3
0
Order By: Relevance
“…This lack of an effect may be partly due to the subtle differences between the objects used in this study. Reflective markings, such as those described by Fang et al (2019), entail much higher reflective capacities than the three spheres we ultimately used. We deliberately selected objects whose reflectance mimics the Plexiglass boxes regularly used for cognitive testing on this species in other experiments.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This lack of an effect may be partly due to the subtle differences between the objects used in this study. Reflective markings, such as those described by Fang et al (2019), entail much higher reflective capacities than the three spheres we ultimately used. We deliberately selected objects whose reflectance mimics the Plexiglass boxes regularly used for cognitive testing on this species in other experiments.…”
Section: Discussionmentioning
confidence: 99%
“…The objects used in this study were selected based on this species’ perception and ecology as recommended by Greggor et al (2015) and on hypotheses derived from previous habituation procedures to experimental apparatuses (see predictions in the introductory part). Previous studies have suggested that reflective surfaces may elicit avoidance in birds and mammals in the wild (Fang et al, 2019) and that removing reflective surfaces may increase welfare in captive cattle (Grandin, 2012). Testing for a neophobic response in this category may thus improve future enrichment programs for captive individuals of this species.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation